2011
DOI: 10.1002/anie.201107053
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry, AFM, and PM‐IRRA Spectroscopy of Immobilized Hydrogenase: Role of a Hydrophobic Helix in Enzyme Orientation for Efficient H2 Oxidation

Abstract: Nickel-iron hydrogenase ([NiFe] Hase) catalyzes hydrogen splitting into protons and electrons, and is a potential biocatalyst in fuel cells.[1] Three FeS clusters aligned as a conductive wire drive electrons from the [NiFe] active site to the surface of the enzyme, where the redox partner (including the electrode) binds. Direct enzyme connection gave access to thermodynamic and kinetic data of enzymatic reactions through direct electron transfer (DET). Mediated electron transfer (MET) allowed recreation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 19 publications
5
71
0
Order By: Relevance
“…In another example, A. aeolicus membrane-bound Hase immobilized on hydrophobic SAM was examined with AFM. Once again, approximately 3 nm high spherical features were observed, thus indicating the presence of a monolayer of enzyme but not which orientation was adopted [142]. A similar result was obtained with another globular enzyme-R. eutropha membrane-bound Hase-immobilized on a gold electrode [149].…”
Section: Microscopysupporting
confidence: 68%
See 2 more Smart Citations
“…In another example, A. aeolicus membrane-bound Hase immobilized on hydrophobic SAM was examined with AFM. Once again, approximately 3 nm high spherical features were observed, thus indicating the presence of a monolayer of enzyme but not which orientation was adopted [142]. A similar result was obtained with another globular enzyme-R. eutropha membrane-bound Hase-immobilized on a gold electrode [149].…”
Section: Microscopysupporting
confidence: 68%
“…This strategy was applied to various enzymes immobilized on thiol-based SAMs and allowed to determine the surface chemistry on the electrode able to promote DET. One can cite relevant studies that analyzed the catalytic efficiency of A. aeolicus [NiFe]-Hase [142] on negative, positive, or hydrophobic SAMs on gold, of D. gigas Hase on positive SAM on gold [143], of R. eutropha [NiFe]-Hase on negative SAM on silver [61], of Trametes hirsuta LAC on neutral hydrophobic SAM on gold [144], of Cerrena unicolor C139 LAC positive SAM on gold [107], or of Myrothecium verrucaria BOD on positive or negative SAMs on gold [145] (Figure 7). In the latter paper, electrochemistry was coupled to SPR demonstrating that the switching between DET over MET when adsorption was performed either on negative or positive SAM was effectively linked to a different enzyme orientation and not to different enzyme loading.…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…We earlier demonstrated that the orientation of immobilized MbH1 cannot be controlled simply by electrostatic interaction because of the absence of a high dipole moment and a charged patch surrounding the distal FeS cluster situated at the surface of the enzyme [28]. In addition, we have shown that a hydrophilic domain near the distal FeS cluster is formed by the trans-membrane helix surrounded by neutral detergent.…”
Section: Carbon Nanotube Coatings For An Enhanced H 2 Oxidation Procementioning
confidence: 95%
“…This hydrogenase from Aa (MbH1) is involved in a complex with a diheme cytochrome b anchored in the membrane, coupling H 2 oxidation to O 2 reduction. Efficient MbH1 immobilization for direct H 2 oxidation was achieved by different strategies like (i) adsorption on pyrolytic graphite electrode (PG) [26], in buffer electrolytes and room temperature ionic liquids [27], (ii) adsorption on self-assembled-monolayer (SAM) modified gold electrode [28], or (iii) connection to a redox polymer film [29]. As MbH1 is membranebound, encapsulation in liposomes was shown to enhance the enzyme stability at the electrode [30].…”
Section: à2mentioning
confidence: 99%